2007
DOI: 10.1016/j.exer.2007.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Traffic of endogenous, transduced, and endocytosed prolactin in rabbit lacrimal acinar cells

Abstract: The rabbit lacrimal gland undergoes an immunophysiological transformation during pregnancy, reminiscent of that of the mammary gland as it prepares to deliver secretory IgA into the nascent fluid product. The contents of TGF-beta and prolactin (PRL) within ductal epithelial cells increase, and their primary localizations shift from the apical to the basal cytoplasm, suggesting a transformation from exocrine to paracrine secretion. Studies with ex vivo acinar cell models demonstrated that elevated PRL suppresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…In non-pregnant females and in males (low prolactin levels) both synthesized and endocytosed prolactin is localized in the apical cytoplasm consistent with secretion by the regulated exocytotic pathway. Cholinergic agonists can then stimulate prolactin secretion via the exocytotic pathway, consistent cholinergic regulation of exocytosis (Wang, Chiu et al 2007). During pregnancy (high prolactin levels) the localization of prolactin changes to the basal cytoplasm consistent with paracrine secretion using the transcytotic pathway.…”
Section: Mechanism Of Lacrimal Gland Protein Secretionmentioning
confidence: 95%
See 3 more Smart Citations
“…In non-pregnant females and in males (low prolactin levels) both synthesized and endocytosed prolactin is localized in the apical cytoplasm consistent with secretion by the regulated exocytotic pathway. Cholinergic agonists can then stimulate prolactin secretion via the exocytotic pathway, consistent cholinergic regulation of exocytosis (Wang, Chiu et al 2007). During pregnancy (high prolactin levels) the localization of prolactin changes to the basal cytoplasm consistent with paracrine secretion using the transcytotic pathway.…”
Section: Mechanism Of Lacrimal Gland Protein Secretionmentioning
confidence: 95%
“…Although specific proteins are secreted by each of these pathways, a single protein can use multiple pathways under different conditions. A complex series of intracellular trafficking pathways elucidated by Mircheff and his collaborators over the years have provided the framework for understanding the complex organization of vesicles in the trafficking pathways of lacrimal gland acinar cells and how these pathways are altered with stimulation for different proteins (Wang, Chiu et al 2007; Wang, Chiu et al 2007). …”
Section: Mechanism Of Lacrimal Gland Protein Secretionmentioning
confidence: 99%
See 2 more Smart Citations
“…Work in several laboratories has demonstrated that epithelial cells in human [33, 34] and rat lacrimal glands [35] express mRNAs for TGF‐β 1 and TGF‐β 2 . Immunohistochemical, physiological [36, 37] and cytophysiological [38, 39] studies indicate that epithelial cells in the interlobular ducts of the rabbit lacrimal gland secrete various cytokines and growth factors to the lumen of the acinus‐duct system, via their apparatus for exocrine protein secretion, and to the underlying stromal space, via, under normal circumstances, the same compartments that secrete autoantigens [38, 39]. Accordingly, TGF‐β might be one of the several factors mediating the anti‐proliferative activity documented by Pockley and Montgomery.…”
Section: Introductionmentioning
confidence: 99%